Os times de melhoria aplicados às empresas de transporte urbano rodoviário de passageiros - Toledo, Rafael Lopes de Abreu Mendes de (2002)
Scenarios indicate that the urban public transportation companies need to think about their management model after so rnuch time away from the productivity improvement process. In this way, the industry shows big opportunities to improve the business processes, by adopting the integrated management systems based on management through quality. This production is the result of an exploratory study, which sought a model to the processes improvement, based on improvernent teams. An analysis was made by using the study of cases methodology in reference of an organization situated in Rio de Janeiro State, Brazil, and whose management system achieved several prizes in the Iast five years. in ali the management teams questionnaires were applied, and the results were analyzed. A profile was also built, based on a conceptual model proposed in the sarne production. The result of this comparative study validates the instrument research, and gets to the conclusion of the importance of the managernent tearns to achieve results more satisfactory inside the organization.